Transporting live silver catfish (Rhamdia quelen) with salt addition does not mitigate fish stress and negatively affects meat quality - ROSA,Sheron Scholze (2019)
Abstract This study evaluated the effects of NaCl added to water during silver catfish (Rhamdia quelen) transportation on stress and meat quality. Physiological indicators of stress (cortisol, glucose, circulating ions and liver glycogen) and meat quality parameters (rigor mortis, pH, instrumental color, psychotropic aerobic count and sensory analysis) were assessed. Adult silver catfish (n=380) were distributed in four experimental groups: T1: non-transported; T2: transported without NaCl water addition; T3: transported with 8.0-g NaCl L–1 water addition; T4: transported with 12.0-g NaCl L–1 water addition. The addition of NaCl was not effective at reducing blood cortisol in silver catfish (P>0.05). An osmotic imbalance was detected as an increase in sodium and calcium levels in the NaCl treatment groups. The 12.0-g NaCl L–1 treatment showed rigor mortis evolution in lesser time than the other treatments, and also presented redder meat color. The NaCl addition in transport water do not mitigate the stress in silver catfish, and in high concentrations (12.0-g L–1) was unfavorable for the homeostasis of fish and have negatively affected its meat quality.